2004
DOI: 10.1051/forest:2004078
|View full text |Cite
|
Sign up to set email alerts
|

Use of chloroplast microsatellites to differentiate oak populations

Abstract: -The possibility to use chloroplast microsatellites (cpSSRs) instead of restriction analysis of PCR-amplified DNA fragments to differentiate oak populations was tested in two economically important tree species: Quercus petraea and Quercus robur. The level and pattern of inter-and intraspecific cpDNA variation were studied over 48 French populations using a total of 24 cpSSR loci. The same pattern of low intrapopulation diversity and high population differentiation was noted with both types of markers, since t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 31 publications
2
30
1
3
Order By: Relevance
“…1995), allowing us to track recolonization processes through seeds. A previous study showed that chloroplast simple sequence repeats (cpSSRs) yield similar genetic patterns to chloroplast polymerase chain reaction‐restriction fragment length polymorphism (cpPCR‐RFLP) at the French scale for Q. petraea and Q. robur (Deguilloux et al . 2004) and, thus, constitute appropriate markers to infer historical recolonization processes in oaks.…”
Section: Introductionmentioning
confidence: 99%
“…1995), allowing us to track recolonization processes through seeds. A previous study showed that chloroplast simple sequence repeats (cpSSRs) yield similar genetic patterns to chloroplast polymerase chain reaction‐restriction fragment length polymorphism (cpPCR‐RFLP) at the French scale for Q. petraea and Q. robur (Deguilloux et al . 2004) and, thus, constitute appropriate markers to infer historical recolonization processes in oaks.…”
Section: Introductionmentioning
confidence: 99%
“…Defining such relatedness is necessary if new phylogeographic studies based on cpSSRs are to be compared to earlier works carried out using PCR-RFLPs. Deguilloux et al (2004) found almost complete redundancy between the haplotypes identified using the two types of markers in French oak populations. Other studies related haplotypes from the two marker systems only partially (Gailing et al 2007b, Neophytou & Michiels 2013.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, they may reveal incomplete concordance with PCR-RFLP when studying the genetic structure of populations. Nonetheless, direct relationships between cpSSR and PCR-RFLP haplotypes is expected since they are fully linked in the chloroplast genome, as previously reported (Deguilloux et al 2004, Gailing et al 2007b, Neophytou & Michiels 2013. However, PCR-RFLPs have low mutation rates and are primarily useful for reconstructing patterns at large geographical scales, while they lack the resolution needed for fine spatial scales studies.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations